To Infuse or Ingest in Human Laboratory Alcohol Research. (15th March 2020) - Cyders, Melissa A.; Plawecki, Martin H.; Corbin, William; King, Andrea; McCarthy, Denis M.; Ramchandani, Vijay A.; Weafer, Jessica; O'Connor, Sean J.
Abstract : Human alcohol laboratory studies use two routes of alcohol administration: ingestion and infusion. The goal of this paper was to compare and contrast these alcohol administration methods. The work summarized in this report was the basis of a 2019 Research Society on Alcoholism Roundtable, "To Ingest or Infuse: A Comparison of Oral and Intravenous Alcohol Administration Methods for Human Alcohol Laboratory Designs." We review the methodological approaches of each and highlight strengths and weaknesses pertaining to different research questions. We summarize methodological considerations to aid researchers in choosing the most appropriate method for their inquiry, considering exposure variability, alcohol expectancy effects, safety, bandwidth, technical skills, documentation of alcohol exposure, experimental variety, ecological validity, and cost. Ingestion of alcohol remains a common and often a preferable, methodological practice in alcohol research. Nonetheless, the main problem with ingestion is that even the most careful calculation of dose and control of dosing procedures yields substantial and uncontrollable variability in the participants' brain exposures to alcohol. Infusion methodologies provide precise exposure control but are technically complex and may be limited in ecological validity. We suggest that alcohol ingestion research may not be the same thing as alcohol exposure research; investigators should be aware of the advantages and disadvantages that the choice between ingestion and infusion of alcohol invokes. Abstract : Human alcohol laboratory studies use two routes of alcohol administration: ingestion and infusion. Choosing the most appropriate method should consider exposure variability, alcohol expectancy effects, safety, bandwidth, technical skills, documentation of alcohol exposure, experimental variety, ecological validity, and cost. Ingestion of alcohol remains common and often preferable, although it yields substantial and uncontrollable variability in brain exposures to alcohol (top panel). Infusion methodologies provide precise exposure control (bottom panel) but are technically complex and may be limited in ecological validity.